A Comparative Study of Indonesian Estimated Rice Production and Consumption - Anggraeni, Tri (Departemen Ilmu Administrasi FISIP UNHAS, 2020)
The permit of two million tons of rice import in 2018 has tickled Indonesia's ability to fulfill its own rice needs. Farmers' anxiety that rice import can affect rice prices proved by its declining. The distribution of imported rice indeed has not been optimal. People say that imports are carried out without proper planning. This study aims to estimate the rice production and consumption data of Indonesia in 2014 to 2019, compare those data, and conclude whether Indonesia needs to import the rice at those years based on the comparison result. Estimating rice production and consumption were carried out using secondary data consisted of paddy production data, per capita rice consumption data, and population projection data which obtained from the website of the Central Statistics Agency (BPS) and/or the Ministry of Agriculture. Based on the comparison result between rice production and consumption data from 2014 to 2019, it can be concluded that from 7 islands in Indonesia, only 2 islands have the estimated rice consumption which always more than the estimated production, namely Maluku and Papua. The total estimated rice consumption in Indonesia is always lower than the estimated production. A rice surplus on a nearby island, Sulawesi, should be able to cover shortages in Maluku and Papua. If the estimated rice consumption in these three islands is totaled, the amount is always smaller than the estimated rice production in these three islands. This is because the production of rice on the island of Sulawesi is very large. The estimated total consumption of rice in 2019 is only 60% of production.